Effect of Butterfly Pea Flower (Clitoria ternatea L.) Kombucha Against Streptococcus viridans - Yuanita, Tamara; Firmansyah, Awang Bagus; Ulfadi , Bakhiitah Thufailah Putri; Prasetyo, Eric Priyo; Wahjuningrum, Dian Agustin (Conservative Dentistry Journal, 2025)
Background: Dental caries is a multifactorial disease driven by the formation of bacterial biofilms, particularly Streptococcus viridans, which contribute to root canal infections if not appropriately managed. Sodium hypochlorite (NaOCl) is commonly used as an irrigant in root canal therapy, but its application is limited due to its toxicity and corrosiveness. Consequently, there is a pressing need for safer and more effective natural alternatives. Kombucha derived from butterfly pea flower (Clitoria ternatea L.) has been identified as a promising candidate with antibacterial and antibiofilm properties due to its bioactive secondary metabolites. The fermentation process involving a symbiotic culture of bacteria and yeast (SCOBY) may further enhance the efficacy of these bioactive compounds. Purpose: This study conducted to analyze the effect of kombucha from butterfly pea flower (Clitoria ternatea L.) on the biofilm of Streptococcus viridans in vitro, utilizing a spectrophotometric method to assess the impact across various concentrations. Methods: An experimental laboratory study was conducted in vitro employing a post-test-only control group design. Kombucha prepared from butterfly pea flower was fermented for periods ranging from 12 to 154 days, followed by dilution into several concentrations (100%, 50%, 25%, 12.5%, 6.25%, 3.12%, and 1.56%) using the dilution method. Direct contact between the kombucha and Streptococcus viridans was established, and the resulting biofilm inhibition was assessed by measuring the Optical Density (OD) using a spectrophotometer at a wavelength of 650 nm. Results: The inhibitory percentage of butterfly pea flower kombucha against Streptococcus viridans biofilm decreased progressively with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.56%. The highest inhibitory percentage was observed at a concentration of 100%. Conclusion: Kombucha of butterfly pea flower (Clitoria ternatea L.) demonstrated potential in inhibiting Streptococcus viridans biofilm formation, with a concentration of 25% determined as the MBIC50. However, an MBEC90 value could not be established, as no biofilm inhibition percentage exceeding 90% was observed in the test results.